Bayesian methods applied to the interpretation of multiple OSL dates: high precision sediment ages from Old Scatness Broch excavations, Shetland Isles - Rhodes, E; Ramsey, C; Outram, Z; Batt, C; Willis, L; Dockrill, S; Bond, J (Elsevier, 2003)
In this paper, we illustrate the ways in which Bayesian statistical techniques may be used to enhance chronological resolution when applied to a series of OSL sediment dates. Such application can achieve an optimal chronological model by incorporating stratigraphic and age information. The application to luminescence data is not straightforward owing to the sources of uncertainty in each date, and here we present one solution to overcoming these difficulties, and introduce the concept of "unshared systematic" errors. Using OSL sediment dates from the site of Old Scatness Broch, Shetland Isles, UK, many measured with a high degree of precision, we illustrate some of the ways in which Bayesian techniques may be applied, as a tool for assessing systematic errors when combined with independent chronological information, and to determine the optimum chronological information for specific events and contexts. We provide a detailed procedure for the application of Bayesian methods to OSL dates using the widely available radiocarbon calibration programme OxCal.